Sources of information about gestational weight gain, diet and exercise among Brazilian immigrant women living in the USA: a cross-sectional study. Issue 17 (27th December 2021) - Lindsay, Ana Cristina; Le, Qun; Nogueira, Denise L; Machado, Márcia MT; Greaney, Mary L
Abstract: Objective: The objective of this study was to assess sources of information about gestational weight gain (GWG), diet and exercise among first-time pregnant Brazilian women in the USA. Design: Cross-sectional survey. Setting: Massachusetts, USA. Participants: First-time pregnant Brazilian women. Results: Eighty-six women, the majority of whom were immigrants (96·5 %) classified as having low acculturation levels (68 %), participated in the study. Approximately two-thirds of respondents had sought information about GWG (72·1 %), diet (79·1 %) and exercise (74·4 %) via the internet. Women classified as having low acculturation levels were more likely to seek information about GWG via the internet (OR = 7·55; 95 % CI 1·41, 40·26) than those with high acculturation levels after adjusting for age and receiving information about GWG from healthcare provider (doctor or midwife). Moreover, many respondents reported seeking information about GWG (67 %), diet (71 %) and exercise (52 %) from family and friends. Women who self-identified as being overweight pre-pregnancy were less likely to seek information about diet (OR = 0·32; 95 % CI 0·11, 0·93) and exercise (OR = 0·33; 95 % CI 0·11, 0·96) from family and friends than those who self-identified being normal-weight pre-pregnancy. Conclusions: This is the first study to assess sources of information about GWG, diet and exercise among pregnant Brazilian immigrants in the USA. Findings have implications for the design of interventions and suggest the potential of mHealth intervention as low-cost, easy access option for delivering culturally and linguistically tailored evidence-based information about GWG incorporating behavioural change practices to this growing immigrant group.